ANFIS Based Solution to the Inverse Kinematics of a 3DOF Planar Manipulator. (2015) - Duka, Adrian-Vasile
Abstract: This paper investigates a method for finding a neuro-fuzzy based solution to the inverse kinematics problem of robotic manipulators. For this purpose, the case of a hypothetical 3 degree of freedom (DOF) planar robot is considered, for which computer simulation is performed in order to outline the effectiveness of the approach. By transforming the inverse kinematics problem to a fitting problem, an Adaptive Neuro-Fuzzy Inference System (ANFIS) is trained using the inverse mapping of the data provided by the forward kinematics and learns, with acceptable accuracy, the end-effecter's localization to joint angles mapping.